CO-DELIVERY OF NATURAL METABOLIC INHIBITORS IN A SELF-MICROEMULSIFYING DRUG DELIVERY SYSTEM FOR IMPROVED ORAL BIOAVAILABILITY OF CURCUMIN - Grill, Alex E. (Drug Deliv Transl Res, 2014)
In spite of its well-documented anticancer chemopreventive and therapeutic activity, the clinical development of curcumin has been limited by its poor oral bioavailability. Curcumin has low aqueous solubility and undergoes extensive first pass metabolism following oral dosing. We hypothesized that oral bioavailability of curcumin can be enhanced by increasing its absorption and decreasing its metabolic clearance simultaneously. To test this hypothesis, we formulated curcumin with naturally occurring UGT inhibitors (piperine, quercetin, tangeretin, and silibinin) in a self-microemulsifying drug delivery system (SMEDDS). Mouse liver microsome studies showed that silibinin and quercetin inhibited curcumin glucuronidation effectively. When dosed orally in mice, the SMEDDS containing curcumin alone increased curcumin glucuronide concentrations in plasma without significantly affecting parent drug concentration. Of the four inhibitors examined in vivo, silibinin significantly improved the C(max) (0.15 μM vs. 0.03 μM for curcumin SMEDDS) and the overall bioavailability (3.5-fold vs. curcumin SMEDDS) of curcumin. Previous studies have shown that silibinin has anticancer activity as well. Thus, co-delivery of silibinin with curcumin in SMEDDS represents a novel and promising approach to improve curcumin bioavailability.